A Blockchain-Based User Authentication Scheme with Access Control for Telehealth Systems. (30th March 2022) - Shi, Shuyun; Luo, Min; Wen, Yihong; Wang, Lianhai; He, Debiao
Abstract : With the development of telecommunication systems and customized monitoring devices, telehealth has been widely used to improve medical quality and reduce overall health costs. However, the convenience of connection between the providers and patients through a public channel also leads to significant security and privacy concerns. Though there have been many authentication schemes designed for secure communications in telecare systems, most of them suffer from malicious attacks or have heavy computation and communication costs. Thus, in this article, we proposed a blockchain-based user authentication scheme integrating with access control and physical unclonable function (PUF). Permissioned blockchain and PUF are used to support secure data sharing across the healthcare service providers and identify the devices, respectively. Security analysis shows that our protocol satisfies the security requirements for telehealth services and is provably secure in the random oracle model. The performance evaluation demonstrates that it has less computation and communication costs compared with three of the latest schemes.